MLHP: A Multi-Level Handoff Prioritization Framework for Service Differentiation in Buffered Systems - Oluwasanya Oyedele; Akinniyi Stellamaris Omowunmi; Akinola Kayode Emmanuel (Methods in Science and Technology Studies, 2026)
In modern wireless networks, efficient handoff strategies are crucial for several services with various Quality of Service (QoS) requirements. However, a significant research gap exists as most current handoff techniques treat all internet traffic uniformly, leading to performance degradation, latency, and glitches for time-sensitive applications like Ultra-Reliable Low Latency Communication (URLLC) during network transitions. To address this, the main objective of this study was to develop the Multi-Level Handoff Prioritization (MLHP) framework specifically for buffered handoff setups. The MLHP system integrates three core components: a multi-level service classifier, a dedicated buffering architecture with dynamic thresholds, and a hybrid scheduling mechanism combining Strict Priority and Weighted Fair Queuing. Simulation results reveal that MLHP significantly outperforms both traditional Non-Prioritized Buffered Handoff (NPBH) and Dynamic Queue Management (DQM) schemes. Key findings indicate that MLHP maintains a low dropping probability of approximately 6% under high handoff frequencies and achieves an aggregate throughput exceeding 44 Mbps during high mobility scenarios, while successfully maintaining sub-10 ms delays specifically for mission-critical URLLC traffic. The broader implications of this study suggest that MLHP provides a scalable and flexible solution for handoff management, effectively meeting the stringent requirements of 5G-and-beyond networks. By ensuring granular service differentiation, the framework enhances overall network reliability and user experience in increasingly heterogeneous mobile environments.